Comparison of Wpeak, VO2peak and the ventilation threshold from two different incremental exercise tests: Relationship to endurance performance - Bentley, D. J.; McNaughton, L. R. (Journal of Science and Medicine in Sport, 2003)
This report presents data comparing the peak rate of oxygen consumption (VO2peak), peak power output (Wpeak) and the ventilation threshold (VT) obtained from two different incremental cycle exercise tests performed by nine well trained triathletes (Mean±SD age 32±3 yrs; body mass 77.4±4.9 kg and height 185±3 cm). Furthermore, the relationship between these variables and the average sustained power output (W) during a 90 min cycle time trial (TT) was also determined. The two incremental exercise tests involved a `short` test, which commenced at 150 W with 30 W increments every 60 s until exhaustion. The second (`long`) incremental test commenced at a power output representing 50% of the Wpeak obtained in the short test. The subjects were then required to increase the power output by 5% every 3 min until exhaustion. The results showed the Wpeak (W) in the short test was significantly (p<0.01) higher than in the long test. However, there was no significant difference in the VO2peak (l·min-1) between the two tests. There was a weak but significant correlation between Wpeak (W) and VO2peak (l·min-1) (r=0.72; p<0.05) in the short (60 s stage) test but not the long (3 min stage) test (r=0.52). There were no significant differences and good agreement between for the heart rate (HR) (b·min-1) and oxygen consumption (VO2) corresponding to the VT. In contrast, the power output (W) corresponding to the VT was significantly different and not comparable between the long and short incremental tests. The cycle TT performance was most correlated to the Wpeak (W) (r=0.94; p<0.01) and the VT (W) (r=0.75; p<0.05) from the long test as well as the VO2peak (l·min-1) obtained from the short incremental test (r=0.75; p<0.01). These data suggest that the length of stages during incremental cycle exercise may influence the Wpeak and in turn the relationship of this variable to VO2peak. Furthermore, the Wpeak obtained from a test incorporating 3 min stage increments represents the best indicator of 90 min cycle performance in well-trained triathletes.